Pengaruh Work Overload Dan Stress Kerja Terhadap Kinerja Karyawan Dengan Kompensasi Sebagai Variabel Intervening Pada PT Teluk Luas - Charli, Chintya Ones; Mahzum, Muhammad (Journal of Computer Science and Information System(JCoInS), 2024)
This research aims to determine the effect of work overload and work stress on employee performance with compensation as an intervening variable at PT Teluk Luas. The approach to this research is quantitative research using saturated samples. Data was obtained using a survey method with a total of 39 respondents who worked at PT Teluk Luas. The analysis used is SEM-PLS which consists of an outer model, inner model and hypothesis testing using Smart-PLS software. The results of this research show that there is an influence of work overload on compensation. There is an influence of compensation on employee performance. There is no influence of work stress on employee performance and compensation. Furthermore, there is the influence of work overload through compensation on employee performance. And there is no influence of work stress on employee performance through compensation at PT Leluk Luas. Excess workload is not a problem for employees at PT Teluk Luas to improve their performance if they receive compensation that is commensurate with the load they have been given.